Unromantic Heroines in the Romantic Stories of Zhang Ailing (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
At a time when most modern Chinese writers were preoccupied with grand topics such as the revolution, the road to national salvation, and resistance against the Japanese aggression, Zhang Ailing (张爱玲, 1920–1995) deals with seemingly trivial, intimate dilemmas of the Chinese during the Second World War. At the center of her attention are the romantic feelings between men and women, and the complex relations within the patriarchal Chinese family. Her heroines, torn between the traditional moral constrictions and desires of their own, their needs, as well as their self-preservation urge in a patriarchal society faced with tumultuous historical events, are represented without any embellishment. Unlike typical representations of women where the most prominent thing about them is their potential with regard to emancipation and women’s liberties, one of the most important Chinese female writers of the twentieth century presented an image of a modern woman who is aware of her limits and tries to strike a balance between preserving her integrity and making compromises in life. In this article, the analysis of the inner world of modern and urbane female characters in two of Zhang Ailings’s short stories, “Love in a Fallen City” (倾城之恋) and “The Golden Cangue” (金锁记), will point out some of the ways in which Chinese women are trying to throw off the schackles of patriarchal society during the dramatic encounter of tradition and modernity
Keywords: romances; tradition; modernity; female characters; compromise